Determinants of longitudinal change in insulin clearance: the Prospective Metabolism and Islet Cell Evaluation cohort - Christine Lee; Stewart B Harris; Anthony J Hanley; Philip W Connelly; Bernard Zinman; Ravi Retnakaran; Zhila Semnani-Azad; Luke W Johnston (BMJ Open Diabetes Research & Care)
Objective To evaluate multiple determinants of the longitudinal change in insulin clearance (IC) in subjects at high risk for type 2 diabetes (T2D).Research design and methods Adults (n=492) at risk for T2D in the Prospective Metabolism and Islet Cell Evaluation cohort, a longitudinal observational cohort, had four visits over 9 years. Values from oral glucose tolerance tests collected at each assessment were used to calculate the ratios of both fasting C peptide-to-insulin (ICFASTING) and areas under the curve of C peptide-to-insulin (ICAUC). Generalized estimating equations (GEE) evaluated multiple determinants of longitudinal changes in IC.Results IC declined by 20% over the 9-year follow-up period (p<0.05). Primary GEE results indicated that non-European ethnicity, as well as increases in baseline measures of waist circumference, white cell count, and alanine aminotransferase, was associated with declines in ICFASTING and ICAUC over time (all p<0.05). There were no significant associations of IC with sex, age, physical activity, smoking, or family history of T2D. Both baseline and longitudinal IC were associated with incident dysglycemia.Conclusions Our findings suggest that non-European ethnicity and components of the metabolic syndrome, including central obesity, non-alcoholic fatty liver disease, and subclinical inflammation, may be related to longitudinal declines in IC.